Strengthening Community Participation in the Information Society Scheme within Cyberspace (Society 5.0) to Enhance the Performance of Public Security and Order Maintenance - Hamid, Supardi (Faculty of Law, Universitas Pekalongan, 2024)
The use of social media by the police is part of the transformation of policing functions in a digital era rule of law state. This study aims to analyse the use of cyberspace by the police in strengthening community participation in maintaining security and public order (harkamtibmas) from the perspective of cyber criminology and the protection of citizens' rights. This study uses a mixed method with an empirical juridical approach through interviews, legal documentation studies, and quantitative surveys conducted in four regional police areas. The results show that social media has functioned as an instrument of public service and digital community participation, but there is still a gap between the police response in cyberspace and the substantive response in the field. This condition has implications for public service accountability and has the potential to cause maladministration. In addition, digital interactions between the police and the community place the police as controllers of personal data, while the operational mechanisms for managing personal data have not been adequately regulated. This study concludes that digital policing must be positioned as a legal practice subject to the principles of legality, accountability, and protection of human rights, and requires the strengthening of an operational regulatory framework in order to optimise public order and security based on public participation.